2022
DOI: 10.1021/acs.jafc.2c04476
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin Alleviates Nonalcoholic Fatty Liver Disease by Regulating the Intestinal Flora and Targeting the AMPK/Nrf2 Signal Axis

Abstract: Nonalcoholic fatty liver disease (NAFLD) is among the most prevalent chronic liver diseases around the globe. The accumulation of lipids in the liver and oxidative stress are important pathological mechanisms of NAFLD. Astaxanthin (AT) is a carotenoid extracted from shrimps and crabs with beneficial biological activities, including anti-oxidative and anti-inflammatory activities. 16S microflora sequencing, H&E staining, and the western blot technique were employed to investigate the impacts of AT on a high-fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 49 publications
(91 reference statements)
1
4
0
Order By: Relevance
“…37 The role of Nrf2 in liver steatosis, inflammation, fibrosis, as well as related therapeutic strategies has been recently summarized by Bukke et al 38 Besides, the studies that the natural plants components alleviate NAFLD via AMPK/Nrf2 pathway have been reported extensively. 36,39,40 In this study, the downregulation in the relative protein level of p-AMPK/AMPK, Nrf2, and HO-1 in HFD-feeding rats was restored by the treatment of PMS, suggesting that PMS activated the AMPK/Nrf2 pathway in HFD-induced NAFLD rats. Zeng et al 28 have reported that PMS promotes the activation of Nrf2/HO-1 pathway in hypoxia/reoxygenation-induced injury.…”
Section: Conflict Of Interest Statementsupporting
confidence: 50%
See 1 more Smart Citation
“…37 The role of Nrf2 in liver steatosis, inflammation, fibrosis, as well as related therapeutic strategies has been recently summarized by Bukke et al 38 Besides, the studies that the natural plants components alleviate NAFLD via AMPK/Nrf2 pathway have been reported extensively. 36,39,40 In this study, the downregulation in the relative protein level of p-AMPK/AMPK, Nrf2, and HO-1 in HFD-feeding rats was restored by the treatment of PMS, suggesting that PMS activated the AMPK/Nrf2 pathway in HFD-induced NAFLD rats. Zeng et al 28 have reported that PMS promotes the activation of Nrf2/HO-1 pathway in hypoxia/reoxygenation-induced injury.…”
Section: Conflict Of Interest Statementsupporting
confidence: 50%
“…Nrf2 plays an important role in neutralizing oxidative stress and conserving redox homeostasis in the cell through the generation of cytoprotective and antioxidant enzymes, such as HO‐1 and NQO1 37 . The role of Nrf2 in liver steatosis, inflammation, fibrosis, as well as related therapeutic strategies has been recently summarized by Bukke et al 38 Besides, the studies that the natural plants components alleviate NAFLD via AMPK/Nrf2 pathway have been reported extensively 36,39,40 . In this study, the downregulation in the relative protein level of p‐AMPK/AMPK, Nrf2, and HO‐1 in HFD‐feeding rats was restored by the treatment of PMS, suggesting that PMS activated the AMPK/Nrf2 pathway in HFD‐induced NAFLD rats.…”
Section: Discussionmentioning
confidence: 64%
“…In particular, the calcium signaling pathway also showed a high enrichment score in GSEA analysis, suggesting ameliorative mitochondrial calcium balance by AX. A previous study showed that the Nrf2-ARE pathway, the most classical signaling pathway for AX activation, is mainly responsible for regulating intracellular antioxidants and maintaining redox balance in mitochondria. Nonetheless, it remains unclear whether AX contributes to maintaining cellular redox balance by activating the Nrf2-ARE pathway, thereby altering calcium signaling molecular events and thus improving the normal function of mitochondria in ALD.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro OA and PAtreated L02 and HepG2 cells; in vivo HFD-fed mice Downregulated SREBP-1c, ACC, FAS, CD36, CPT1α, FOXA, PGC1α, TNF-α, and IL-1β; upregulated AMPK and Nrf2 [281][282][283] 76 This article is protected by copyright. All rights reserved.…”
Section: Accepted Manuscriptmentioning
confidence: 99%